Encryption of Text Message on Audio Steganography Using Combination Vigenere Cipher and LSB (Least Significant Bit) - Mulyono, Ibnu Utomo Wahyu; Susanto, Ajib; Anggraeny, Tiara; Sari, Christy Atika (Universitas Muhammadiyah Malang, 2019)
Ã‚Â The growing information technology is very rapidly, the more evolving crime techniques to find information that is confidential. The Internet is one of the main media in disseminating information. The use of security on the internet still needs to be developed. Based on these problems, the type of research undertaken in the writing of this final task is the type of experimental research by developing methods that have been done by previous researchers to hide secret data that is inserted into the audio * .wav so that the security and confidentiality of data can be guaranteed. data security can be done with various methods, including cryptography and steganography. Cryptography is a technique for encrypting messages and steganography is a message concealment technique. This insertion type uses binary ASCII character code. In the cryptographic process, using the Vigenere Cipher algorithm and in the steganography, process using the algorithm (LSB) Least Significant Bits. The merger of the two techniques resulted in a better new digital image security system and increased the value of MSE, PSNR and Execution time. Then the test results in the evaluation using BER and histogram analysis. Good audio quality has a minimum value of 30 dB PSNR. In the embedding process using combinations of vigenere and LSB methods, Audio 15 is the best audio compared to other audio. Audio 15 has a smaller MSE (0.001656) value and a larger PSNR (124.138499) value than any other audio when embeded messages *.txt file with character 4096.